Amniotic band syndrome and limb body wall complex in Europe 1980–2019. Issue 4 (30th December 2022) - Bergman, Jorieke E. H.; Barišić, Ingeborg; Addor, Marie‐Claude; Braz, Paula; Cavero‐Carbonell, Clara; Draper, Elizabeth S.; Echevarría‐González‐de‐Garibay, Luis J.; Gatt, Miriam; Haeusler, Martin; Khoshnood, Babak; Klungsøyr, Kari; Kurinczuk, Jennifer J.; et al.
Abstract: Amniotic band syndrome (ABS) and limb body wall complex (LBWC) have an overlapping phenotype of multiple congenital anomalies and their etiology is unknown. We aimed to determine the prevalence of ABS and LBWC in Europe from 1980 to 2019 and to describe the spectrum of congenital anomalies. In addition, we investigated maternal age and multiple birth as possible risk factors for the occurrence of ABS and LBWC. We used data from the European surveillance of congenital anomalies (EUROCAT) network including data from 30 registries over 1980–2019. We included all pregnancy outcomes, including live births, stillbirths, and terminations of pregnancy for fetal anomalies. ABS and LBWC cases were extracted from the central EUROCAT database using coding information responses from the registries. In total, 866 ABS cases and 451 LBWC cases were included in this study. The mean prevalence was 0.53/10, 000 births for ABS and 0.34/10, 000 births for LBWC during the 40 years. Prevalence of both ABS and LBWC was lower in the 1980s and higher in the United Kingdom. Limb anomalies and neural tube defects were commonly seen in ABS, whereas in LBWC abdominal and thoracic wall defects and limb anomalies were most prevalent. Twinning was confirmed as a risk factor for both ABS and LBWC. This study includes the largest cohort of ABS and LBWC cases ever reported over a large time period using standardized EUROCAT data. Prevalence, clinical characteristics, and the phenotypic spectrum are described, and twinning is confirmed as a risk factor.